“Can Two Walk Together, Except They be Agreed?”: Psychology and Theology — a Journey Together or Paths Apart? - Clouse, Bonnidell (Journal of psychology and theology, 1997)
The integration of psychology and theology is likened to a journey in which two people share their ideas. Sometimes there is agreement and the two walk the same path; sometimes no agreement is possible and the two must go their separate ways. The psychologies of psychoanalysis, learning psychology (behaviorism), cognitive psychology, and humanistic psychology are evaluated using Scripture as the criterion for acceptance or rejection of basic ideas and methodology.